2011
DOI: 10.1016/j.cub.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The Exoribonuclease Nibbler Controls 3′ End Processing of MicroRNAs in Drosophila

Abstract: Summary microRNAs are endogenous non-coding small RNAs with important roles in many biological pathways; their generation and activity are under precise regulation [1–3]. Emerging evidence suggests that miRNA pathways are precisely modulated with controls at the level of transcription [4–8], processing [9–11] and stability [12,13], with miRNA deregulation linked with diseases [14] and neurodegenerative disorders [15]. In the Drosophila miRNA biogenesis pathway, long primary miRNA transcripts undergo sequential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
140
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(148 citation statements)
references
References 33 publications
8
140
0
Order By: Relevance
“…Our results show that 3′ adenylation of oncomiR miR-21 by the nucleotidyl transferase PAPD5 may similarly lead to its degradation by targeting it for 3′ end trimming by exoribonuclease PARN. This enzyme thus is a human ortholog of the exonuclease Nibbler, which was recently discovered to trim the 3′ ends of miRNAs in Drosophila (43,44). PARN was recently also shown to trim the 3′ arm of human pre-miR-451 in the 3′-to-5′ direction as the final step in the maturation pathway of this miRNA (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that 3′ adenylation of oncomiR miR-21 by the nucleotidyl transferase PAPD5 may similarly lead to its degradation by targeting it for 3′ end trimming by exoribonuclease PARN. This enzyme thus is a human ortholog of the exonuclease Nibbler, which was recently discovered to trim the 3′ ends of miRNAs in Drosophila (43,44). PARN was recently also shown to trim the 3′ arm of human pre-miR-451 in the 3′-to-5′ direction as the final step in the maturation pathway of this miRNA (50).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several posttranscriptional mechanisms have been uncovered that enable the fine-grained regulation of individual miRNAs beyond the canonical maturation pathway (3,43,44). Next-generation sequencing of miRNAs has revealed a wide variety of miRNA variants that may be produced by differential excision by DICER1 or nucleotide additions to the 3′ ends of miRNAs or their precursors (11,45).…”
Section: Discussionmentioning
confidence: 99%
“…Following acceptance of this work, the Bonini and Zamore labs reported that the 39-59 exoribonuclease Nibbler trims the 39 ends of Drosophila miRNAs (Han et al 2011;Liu et al 2011).…”
Section: Note Added In Proofmentioning
confidence: 99%
“…associated neurodegeneration in Drosophila revealed an intriguing pattern of miR-34 isoforms: Although multiplelength isoforms of miR-34 are generated, only the short isoform accumulates with age (Liu et al 2012). Furthermore, the generation of isoforms of miR-34 requires 39 end trimming by a novel 39-to-59 exonuclease, Nibbler (Nbr) (Han et al 2011;Liu et al 2011), highlighting the potential importance of regulation of miRNA length in age-associated processes.…”
mentioning
confidence: 99%